Biodiversity conservation policy reform and reconciliation in Canada: an analysis of the pathway to Canada target 1 through the policy cycle model - Tamufor, N. Emmanuel; Roth, Robin; MacDonald, David B. (Frontiers in Environmental Science, 2025)
In this article, we conduct an analysis of the Pathway to Canada Target 1 biodiversity conservation policy process to determine its level of inclusivity towards Indigenous Peoples and their knowledge systems. Also known simply as the Pathway, the policy focuses on Target 1 of Canada’s efforts to meet Aichi Target 11 of the Convention on Biological Diversity by 2020. The study aims to showcase the importance and meaningfulness of Indigenous involvement in the policy process. Simply including Indigenous actors does not automatically mean that their knowledge contributions to the policy were considered. Knowing why, when, and how Indigenous Peoples were engaged in the policy process helps us to see the role their presence and contributions played in co-producing policy knowledge for informing the Pathway to Canada Target 1 policy process. This is fundamental in reconciliation and in the improvement of conservation policies. After a review of the history and structure of the Pathway, paying attention to the importance of building relationship with Indigenous Peoples early in the policy process, we use the policy cycle model, outlining five stages of the policy process, to enable our analysis. While we have chosen the policy cycle model as a general framework for analyzing the stages of the policy process, it is a Western model, which falls short in its ability to reflect Indigenous worldviews adequately. Its use reveals, however, the degree of Indigenous engagement in each of the stages, demonstrating that the Pathway to Canada Target 1 did engage Indigenous Peoples at certain stages, in ways potentially reflective of what the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) and the Truth and Reconciliation Commission of Canada (TRC) Calls to Action demand. We conclude with recommendations for more collaborative governance in policymaking that would be more attentive to including Indigenous Peoples and their knowledge systems at all stages of the policy cycle.